Avaliação do teste de polarização fluorescente para discriminar títulos sorológicos de bezerras vacinadas com amostras B19 DE Brucella abortus - Guilherme Canhestro de Faria (2010)
Tests for serologic diagnosis of bucellosis recommended by the Brazilian National Program for the Control and Eradication of Bovine Brucellosis and Tuberculosis (PNCEBT) were compared with the Fluorescent Polarization Assay regarding the ability to discriminate serologic titles arising from the S19 vaccination. The 93 calves used in this experiment were originated from a brucellosis-free dairy farm according to the Brazilian Ministry of Agriculture, Livestock, and FoodSupply (MAPA). The serum samples were obtained just before the vaccination and 3, 6, 9, and 12 months after that. Specificity values for each tests as well agreements and Kappa index values were calculated. The positive correlation between Complement Fixation Test and age atvaccination and Zebu blood degree was evaluated by Spearmen Coefficient and Cohort Study. The Specificity coefficient ranged from 41.94 to 94.57%, 62.37 to 97.83%, 69.89 to 97.83%, and 73.34 to 95.65%, respectively, for the Rose-Bengal Test (RBT), 2-Mercaptoetanol (2-ME),Complement Fixation Test (CFT) and Fluorescent Polarization Assay (FPA). Regarding to the agreement between the tests, the bests values were obtained for the CFT and 2-ME relationship, that was considered perfect nine months after vaccination (k=1.0). The FPA test only presents good agreement with two recommended confirmatory tests of PNCEBT nine months after vaccination (k>0.6). Calves with higher Zebu blood degree and late vaccinated presented significantly higher positive results